Cytomorphological Pattern of Lymph Node Swelling in Tertiary Care Unit - Humera Shahzad, Noshaba Rahat, Muhammad Anwer, Humera Kashif, Shaista Gul, Zumrud Momin (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Tubercular lymphadenitis is one of the most common causes of lymph node enlargement in developing countries. Fine needle aspiration cytology is a simple cost-effective, Rapid and reliable technique and first line investigation for diagnosis of superficial and deep lesion. Aim and objective: of our study was to evaluate the common cytomorphological pattern of lymph node swelling in pathology department of BMSI, Jinnah post graduate medical centre Karachi. Materials and methods: Cross sectional study was conducted at BMSI, Jinnah Post Graduate Institute Karachi. During the period of January to December, 2021, total 350 lymph node swelling were aspirated smear and cell block prepared Aspiration done with 22 to 24 needle gauge syringe.one slide is stained with the diff quick stain and evaluated for diagnostic material inadequate materials were re-aspirated at the time of FNA, three slides were stained with heamotoxylin and eosin stain. Cell block prepared. Results: Total 350 lymph node swelling were aspirated during study time out of which 203(58%) cases diagnosed as chronic granulomatous inflammation, 43(12.3%) cases diagnosed as necrotizing inflammation. 37(10.6%) case diagnosed as abscess and 22(6.3%) cases as reactive hyperplasia, 39(11.1%) cases as metastatic lesions. Conclusion: Chronic granulomatous inflammation is a heavy burden of lymphadenopathy in our setup followed by necrotizing inflammation